2019
DOI: 10.3390/ma12050713
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Synthesis of Rare-Earth Modified Titania: Influence on Phase Composition, Optical Properties, and Photocatalytic Activity

Abstract: In order to expand the use of titania indoor as well as to increase its overall performance, narrowing the band gap is one of the possibilities to achieve this. Modifying with rare earths (REs) has been relatively unexplored, especially the modification of rutile with rare earth cations. The aim of this study was to find the influence of the modification of TiO2 with rare earths on its structural, optical, morphological, and photocatalytic properties. Titania was synthesized using TiOSO4 as the source of titan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 55 publications
2
32
0
3
Order By: Relevance
“…They concluded that the binder inclusion did not significantly enhance the properties of the photocatalytic paints concerning VOC emissions. Nejc Rozman et al prepared rare earth element (such as La, Gd, and Ce) modified TiO2 and assessed the photocatalytic degradation of a few VOCs [162]. A reactor comprising of a gas pump and pipes was set up to understand the degradation kinetics using Fourier-transform infrared spectroscopy.…”
Section: Tio 2 Based Photocatalytic Composites For Voc Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the binder inclusion did not significantly enhance the properties of the photocatalytic paints concerning VOC emissions. Nejc Rozman et al prepared rare earth element (such as La, Gd, and Ce) modified TiO2 and assessed the photocatalytic degradation of a few VOCs [162]. A reactor comprising of a gas pump and pipes was set up to understand the degradation kinetics using Fourier-transform infrared spectroscopy.…”
Section: Tio 2 Based Photocatalytic Composites For Voc Removalmentioning
confidence: 99%
“…They concluded that the binder inclusion did not significantly enhance the properties of the photocatalytic paints concerning VOC emissions. Nejc Rozman et al prepared rare earth element (such as La, Gd, and Ce) modified TiO 2 and assessed the photocatalytic degradation of a few VOCs [ 162 ].…”
Section: Volatile Organic Compoundsmentioning
confidence: 99%
“…These doped oxides are commonly used for a wide range of applications, such as sunscreen cosmetics, magneto-optical devices, catalysts, biomarkers, colorant for special glasses, solid electrolytes, etc. [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The impurity energy levels act as trapping centers for photogenerated electrons and holes, thereby favoring charge separation and reducing the electron-hole recombination [118][119][120][121]. Among these, the La dopant in titania is studied most frequently, followed by Ce doping, in recent years [116][117][118][119][120][121][122]. Kasinathan et al reported that cerium doping suppresses the recombination of photogenerated electron-hole pairs in titania and promotes a red-shift in its band gap transition.…”
Section: Metal Dopingmentioning
confidence: 99%
“…Mo 6+ + e − → Mo 5+ (3) From the literature, rare earth metal ions are effective in extending the recombination time of charge carriers and improving their separation efficiency. Rare earth metals, such as cerium (Ce), lanthanide (La), erbium (Er) and ytterbium (Yb), with 4f, 5d, and 6s electrons are good dopants for modifying the electronic structure and optical properties of titania [116,117]. Rare earth dopants introduce several impurity energy levels due to the introduction of orbitals between the conduction and valence bands.…”
Section: Metal Dopingmentioning
confidence: 99%